Preparation method and application of high-specific-volume conjugated carbonyl organic compound material

By using conjugated carbonyl organic compound materials and using O atoms to coordinate metal ions, reversible energy storage is achieved, which solves the problems of low yield and serious attenuation of organic electrode materials. By optimizing the electrolyte and electrode sheet processes, the whole battery is improved Loading and cycling performance.

CN119409563APending Publication Date: 2025-02-11NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411488167.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing organic electrode materials have problems such as low single production, difficulty in amplification production, dissolving in electrolyte, resulting in severe attenuation, and difficulty in applying to the entire battery.

Method used

The conjugated carbonyl organic compound material is used to coordinate metal ions by O atoms to achieve reversible energy storage, and the specific capacity and cyclic stability of the material are improved through specific preparation methods and electrolyte formulations.

Benefits of technology

The organic electrode materials with high specific capacity and high voltage are achieved, which solves the problems of low yield and serious attenuation, and improves the load capacity and cycling performance of the entire battery by optimizing the electrolyte and pole sheet processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409563A_ABST
    Figure CN119409563A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a high-specific-volume conjugated carbonyl organic compound material which can be used as a positive electrode material in an alkali metal battery and has large-scale synthesis potential. The material realizes reversible energy storage by utilizing O atoms to coordinate metal ions, has the advantages of multiple reaction sites, intramolecular conjugated structures and high specific capacity, the specific capacity is higher than that of most of current conjugated carbonyl compounds, the theoretical capacity is 449mAh / g, the actual capacity is 442mAh / g, and the voltage is higher in an organic N-type material. The material can be synthesized through simple reaction, and is low in reaction temperature, simple in condition and easy to amplify. And the electrolyte concentration is regulated and controlled to obtain a formula capable of inhibiting micromolecule dissolution and improving the cycle retention rate. And the lithium metal soft package battery is assembled, and the application potential is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery positive electrode materials, and in particular to a preparation method and application of a high specific capacity conjugated carbonyl organic compound material. Background Art

[0002] With the development of science and technology, the demand for electric energy is increasing, and battery technology is developing rapidly. As a means of energy storage, rechargeable lithium batteries are valued for their advantages such as high energy density and long cycle life. They have also been widely used in portable electronic devices, electric vehicles, energy storage stations and other fields. Commercial cathode materials are mostly inorganic materials, such as LiCoO2, LiNi x Co y Mn z O2 and LiFePO4, etc., with the increase in demand, their shortcomings such as high cost, limited element reserves, and environmental unfriendliness are exposed. In addition, the lithium storage method of inorganic materials depends on the intercalation and deintercalation of lithium ions between layers, and their capacity and energy density are close to the theoretical upper limit. Therefore, metal-free organic electrode materials are considered to have broad application prospects in the field of energy storage due to their unique properties and advantages, and are expected to become an important component of the next generation of high-performance batteries with the continuous advancement of battery technology.

[0003] Organic electrode materials are composed of elements such as carbon, hydrogen, oxygen, and nitrogen. They can often be obtained from natural products and biomass, and have the advantages of low price and environmental friendliness. In the 1970s, research on organic electrode materials focused on conductive polymers such as polyacetylene and polyaniline, but they had problems such as low specific capacity and low energy density. In the past decade, research on organic electrode materials has risen again, mainly focusing on molecules with functional groups such as carbonyl, imine, carboxylic acid, and polysulfide. The structure of such molecules is flexible and designable, and the energy storage mechanism is based on the redox reaction of organic molecules, so it is expected to achieve a higher specific capacity. The research on organic electrode materials is in a rapid development stage, and its potential application value and challenges are jointly promoting innovation and breakthroughs in this field. The main problems faced by organic electrode materials are low single-time yield, difficulty in scale-up production, dissolution in the electrolyte leading to severe attenuation, and difficulty in application to full batteries. In view of the problem of scale-up production, some organic synthesis operations are complex and the conditions are harsh, which will lead to a decrease in yield after expanding the feed. For the dissolution problem, existing common solutions include salt formation, polymerization, and carbon material loading, etc., but all of them have the problem of reducing capacity. Therefore, modification of the electrolyte is an important strategy to solve this problem. For full batteries, organic materials have low tap density and poor conductivity, making it difficult to achieve high loading, and optimization is needed in terms of film making process and electrode composition. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a conjugated carbonyl organic compound material and a soft-pack battery, which can be used as a positive electrode material in an alkali metal battery. The purpose is to solve the problems of low single-time yield of organic electrode materials, difficulty in scale-up production, severe attenuation caused by dissolution in the electrolyte, and difficulty in application to full batteries.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a conjugated carbonyl organic compound material, which utilizes O atoms to coordinate metal ions to achieve reversible energy storage, has multiple reaction sites, and has a conjugated structure within the molecule. It has the advantage of high specific capacity, which is higher than most current conjugated carbonyl compounds, and has a higher voltage among organic N-type materials. The molecular formula of the conjugated carbonyl organic compound material is C 14 H6O4.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned conjugated carbonyl organic compound material, comprising the following steps: under the protection of argon, dispersing the raw material 2,6-dihydroxyanthracene and the oxidant phenylselenous anhydride in anhydrous tetrahydrofuran respectively, adding the liquid containing 2,6-dihydroxyanthracene dropwise to the liquid containing phenylselenous anhydride in the second step, heating for reaction, cooling and standing, evaporating the liquid under reduced pressure, recrystallizing, washing, and vacuum drying to obtain the conjugated carbonyl organic compound material.

[0007] Furthermore, in the preparation method of the present invention, the dosage of the raw materials is: 7.5 mmol of 2,6-dihydroxyanthracene is added to 100 ml of anhydrous tetrahydrofuran; 15 mmol of phenylselenous anhydride is added to 150 mL of anhydrous tetrahydrofuran.

[0008] Furthermore, in the preparation method of the present invention, the reaction is carried out by heating at 60° C. under an argon atmosphere for 4 hours.

[0009] Furthermore, in the preparation method of the present invention, the solvent used for recrystallization is 1,4-dioxane.

[0010] Furthermore, in the preparation method of the present invention, the crystals obtained by recrystallization are washed with ethanol and vacuum dried at 70°C.

[0011] The present invention provides an alkali metal ion battery, characterized in that the electrode material of one electrode or multiple electrodes is the above-mentioned small molecule conjugated carbonyl compound organic material.

[0012] Furthermore, the alkali metal is lithium, sodium or potassium.

[0013] The present invention provides a high-concentration electrolyte, which can inhibit the dissolution of the above-mentioned small molecule conjugated carbonyl compound organic material and improve the cycle retention rate. In the high-concentration electrolyte, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), the solvent is tetraethylene glycol dimethyl ether (G4), and the concentration is 3 mol / L.

[0014] The present invention provides a high-load electrode made of the above-mentioned small molecule conjugated carbonyl compound organic material, using PTFE as a binder, single-layer graphene and carbon nanotubes; the mass ratio of the small molecule conjugated carbonyl compound organic material, single-layer graphene, carbon nanotubes and PTFE is 7:1:1:1.

[0015] The present invention also provides a lithium metal soft-pack full battery made according to the above-mentioned high-load electrode piece.

[0016] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:

[0017] (1) The conjugated carbonyl compound organic material provided by the present invention is composed of carbon, hydrogen and oxygen elements and has the advantage of being environmentally friendly compared with inorganic materials.

[0018] (2) The conjugated carbonyl organic compound material provided by the present invention utilizes O atoms to coordinate metal ions to achieve reversible energy storage, has multiple reaction sites, and has a conjugated structure within the molecule. It has the advantage of high specific capacity, which is higher than most of the current conjugated carbonyl compounds, and has a higher voltage among organic N-type materials.

[0019] (3) The preparation method of the conjugated carbonyl organic compound material provided by the present invention is simple, which solves the problem that organic materials are difficult to scale up.

[0020] (4) The high-concentration electrolyte provided by the present invention reduces the dissolution of organic positive electrode materials and improves their cycle stability.

[0021] (5) The electrode manufacturing process and formula provided by the present invention achieve a higher loading capacity, and the electrode can be used to assemble lithium metal soft-pack batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The molecular structure and lithium storage process schematic diagram of Example 1 provided by the present invention;

[0023] Figure 2 For embodiment 1 provided by the present invention 1 H NMR spectrum;

[0024] Figure 3 The infrared spectrum of Example 1 provided by the present invention;

[0025] Figure 4The first cycle constant current charge and discharge curves of Example 2 and Comparative Example 1 provided by the present invention;

[0026] Figure 5 The cycle performance diagram of Example 2 provided by the present invention;

[0027] Figure 6 This is the first cycle constant current charge and discharge curve of Example 3 provided by the present invention;

[0028] Figure 7 This is a cycle performance diagram of Comparative Example 2 provided by the present invention. DETAILED DESCRIPTION

[0029] The present invention will be further explained below through the accompanying drawings and specific examples. The following examples are only used as an illustration and should not be understood as limiting the scope of the present invention. The protection scope of the present invention is not limited to the following embodiments.

[0030] Example 1

[0031] A small molecule conjugated carbonyl compound, the molecular formula of which is C 14 H6O4, this material uses O atoms to coordinate metal ions to achieve reversible energy storage, has multiple reaction sites, and has a higher specific capacity than most current conjugated carbonyl compounds. Figure 1 Schematic diagram of the molecular structure and lithium storage process of Example 1.

[0032] The preparation method of the conjugated carbonyl organic compound comprises the following steps: under the protection of argon, adding 2,6-dihydroxyanthracene (1.578 g, 7.5 mmol) to 100 mL of anhydrous tetrahydrofuran; adding phenylselenous anhydride (5.4 g, 15 mmol) to 150 mL of anhydrous tetrahydrofuran; dropping the liquid obtained in the first step into the liquid in the second step, stirring at 60° C. for 4 hours, cooling and standing overnight; evaporating the liquid under reduced pressure, recrystallizing with 1,4-dioxane, washing the solid with ethanol, and vacuum drying at 70° C. to obtain a red product ATO. Figure 2 and 3 For Example 1 1 H NMR spectrum and IR spectrum.

[0033] Example 2

[0034] The present invention provides application of the above material in an alkali metal ion battery and adjusts the electrolyte formula to improve its cycle performance.

[0035] The preparation method of the alkali metal ion battery in this embodiment is as follows: 50wt% of the electrode material ATO described in Example 1, 35wt% of Ketjen black, 5wt% of single-layer graphene physical method, and 10wt% of PTFE are rolled onto a titanium mesh with a diameter of 10mm using a rolling process, and dried at 70℃ for 12h. The active material loading is about 1.5-2mg / cm 2 .

[0036] CR2025-type button cells were assembled in a glove box filled with argon (water and oxygen were less than 0.1ppm). The specific assembly method is: start from the negative electrode shell, add Li metal negative electrode, Celgard 2400 separator, electrolyte, positive electrode, gasket, shrapnel, positive electrode shell in sequence, and finally use 0.94T pressure to encapsulate the battery. The electrolyte formula is 3M LiTFSI G4, and the amount of electrolyte used for each button cell is 60μL. Electrochemical performance tests were carried out.

[0037] Attached Figure 3 It shows that the ATO material has a specific capacity of up to 442 mAh / g in the first cycle, and the discharge medium voltage is about 2.5 V, which can exert 98% of the theoretical specific capacity (449 mAh / g), which is higher than the specific capacity of comparative example 1 (364 mAh / g).

[0038] Attached Figure 4 It shows that the capacity retention rate of ATO material is 65.7% after 160 cycles in 3M LiTFSI G4 electrolyte, and the coulombic efficiency is close to 100%. This electrolyte can improve the cycling performance of organic small molecules.

[0039] Example 3

[0040] In order to study the value of ATO cathode materials in practical applications, the present invention assembled a soft-pack ATO-Li full battery. The cathode contains 70wt% active ATO, 10wt% carbon nanotubes, 10wt% single-layer graphene and 10wt% PTFE binder. The active material content is about 8.6mg / cm 2 The electrolyte formula is 1M LiTFSI G4. The performance test voltage of the battery is 1.3-3.6V and the current density is 22.5mA / g.

[0041] Attached Figure 5 The battery has a discharge capacity of 170 mAh, close to the design capacity of 209 mAh, and a discharge medium voltage of 2.3 V. Based on the mass of ATO in the positive electrode, the energy density of the whole battery is 782 Wh / kg.

[0042] Comparative Example 1

[0043] A small molecule conjugated carbonyl compound, pyrene-4,5,9,10-tetraketone (PTO), was made into a battery according to the method described in Example 2 and the electrochemical performance was tested.

[0044] Comparative Example 2

[0045] Common commercial electrolyte, the formula is 1M LiPF6 EC / DEC (1:1). Batteries were made according to the method described in Example 2 and electrochemical performance tests were performed.

[0046] Attached Figure 7 It shows that the cycling performance of ATO material in 1M LiPF6 EC / DEC (1:1) electrolyte is very poor, and the capacity retention rate after 40 cycles is 24.1%.

[0047] Through the above embodiments, the present invention provides a small molecule conjugated carbonyl compound positive electrode material C 14 The preparation method of H6O4, at the same time, provides the application of the material in alkali metal ion batteries, and studies the value of the positive electrode material in practical applications. The preparation method of the conjugated carbonyl organic compound material provided by the present invention is simple, which solves the problem that organic materials are not easy to scale up. And the small molecule conjugated carbonyl compound positive electrode material obtained by the present invention utilizes O atoms to coordinate metal ions to achieve reversible energy storage, has multiple reaction sites, intramolecular conjugated structure, has the advantage of high specific capacity, and the specific capacity is higher than most current conjugated carbonyl compounds, and the voltage is higher in organic N-type materials. The high-concentration electrolyte provided by the present invention reduces the dissolution of organic positive electrode materials and improves their cycle stability. In practical applications, by comparison, it can be seen that the ATO positive electrode material in Example 3 has a specific capacity of up to 442mAh / g in the first cycle, and the discharge medium voltage is about 2.5V, which can exert 98% of the theoretical specific capacity (449mAh / g), which is higher than the specific capacity (364mAh / g) of Comparative Example 1. At the same time, the capacity retention rate of the ATO material in the 3M LiTFSI G4 electrolyte after 160 cycles is 65.7%, and the coulombic efficiency is close to 100%. However, the cycle performance of the common electrolyte formula in Comparative Example 2 is very poor, and the capacity retention rate after 40 cycles is 24.1%.

[0048] Based on the above embodiments, the present invention provides a method for preparing a conjugated carbonyl organic compound material and a soft-pack battery, which can be used as a positive electrode material in an alkali metal battery, and can solve the problems of low single-time yield, difficulty in scale-up production, severe attenuation caused by dissolution in the electrolyte, and difficulty in application to a full battery. At the same time, as an organic material, it also has the advantages of being green, environmentally friendly, and low-cost compared to inorganic materials, and is expected to be widely used in the new generation of battery technology, showing great potential.

Claims

1. A method for preparing a high specific volume conjugated carbonyl organic compound material, characterized in that The method comprises the following steps: under the protection of argon, dispersing the raw material 2,6-dihydroxyanthracene and the oxidant phenylselenous anhydride in anhydrous tetrahydrofuran respectively, dropping the liquid containing 2,6-dihydroxyanthracene into the liquid containing phenylselenous anhydride in the second step, heating for reaction, cooling and standing, evaporating the liquid under reduced pressure, recrystallizing, washing and vacuum drying to obtain a conjugated carbonyl organic compound material. The positive electrode material has a molecular formula of C 14 H6O4, this material uses O atoms to coordinate metal ions to achieve reversible energy storage and has multiple reaction sites.

2. The preparation method according to claim 1, characterized in that: The dosage of the raw materials is as follows: 7.5 mmol of 2,6-dihydroxyanthracene is added to 100 ml of anhydrous tetrahydrofuran; 15 mmol of phenylselenous anhydride is added to 150 ml of anhydrous tetrahydrofuran.

3. The preparation method according to claim 1, characterized in that The mixture was heated to 60°C under an argon atmosphere for 4 hours.

4. The preparation method according to claim 1, characterized in that: The solvent used for recrystallization was 1,4-dioxane.

5. The preparation method according to claim 1, characterized in that: The crystals obtained by recrystallization were washed with ethanol and dried at 70°C in vacuo.

6. An alkali metal ion battery, characterized in that: The electrode material of one or more electrodes is a small molecule conjugated carbonyl compound organic material prepared by the method described in any one of claims 1 to 5.

7. An alkali metal ion battery according to claim 7, characterized in that: The alkali metal is lithium, sodium or potassium.

8. A high-concentration electrolyte capable of inhibiting the dissolution of the positive electrode material prepared by the method according to any one of claims 1 to 5, characterized in that: In the high-concentration electrolyte, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide LiTFSI, the solvent is tetraethylene glycol dimethyl ether G4, and the concentration is 3 mol / L.

9. A high-load pole piece, characterized in that: The positive electrode material comprises a small molecule conjugated carbonyl compound organic material prepared by any one of claims 1 to 5, polytetrafluoroethylene (PTFE) is used as a binder, and a single-layer graphene and carbon nanotube are used to make a high-load electrode; The ratio of the positive electrode material, single-layer graphene, carbon nanotubes and PTFE is 7:1:1:

1.

10. The use of the high-load pole piece according to claim 9, characterized in that Used to make lithium metal soft-pack full batteries.